(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Derivatives markets in India were introduce about seven years ago and futures Options markets have become an extremely important trading instrument throughout world tlnancial sectors. In our country. India, a Futures Options Market is playing very important role for various category of investor’s right from retail to institutional investors. In this thesis I discuss the role of derivatives markets in terms of price discovery and volatility over a cash market. Paper outlines legal, financial. And structural framework of Index futures contract trading on the National Stock Exchange of India (NSE). I offer a summary for price discovery and volatility in NSE CNX Nifty Index and Nifty Index futures markets. Any study on Index futures trading must include a discussion of the theoretical framework of futures markets institutions, operation mechanisms. and other features of a well organized futures market must also be analyzed. Benchmark indexes require special attention. As they represent the underlying assets of overall markets. I review the techniques of price discovery and volatility and the various factors that innocence it. I operate on the assumption that Indexes are suitable instruments for serving as a foundation of futures contracts. I explain specification and pricing techniques of Index futures and argue that they may indeed represent a good alternative for managing stock market risk.